Biochemical and antioxidant activity of wild edible fruits of the eastern Himalaya, India - Rymbai, Heiplanmi; Verma, Veerendra Kumar; Talang, Hammylliende; Assumi, S. Ruth; Devi, M. Bilashini; Vanlalruati,; Sangma, Rumki Heloise CH.; Biam, Kamni Paia; Chanu, L. Joymati; Makdoh, Badapmain; Singh, A. Ratankumar; Mawleiñ, Joiedevivreson; et al. (Frontiers in Nutrition, 2023)
The eastern Himalayas are one of the important hotspots of global biodiversity, having a rich diversity of wild edible fruit trees. The fruits of these tree species have been consumed by the tribal people since time immemorial. However, there is limited information available on the biochemical and antioxidant properties of the fruits. Therefore, the present investigation was undertaken to study the physico-chemical and antioxidant properties of the nine most important wild fruit trees. Among the species, Pyrus pashia had the maximum fruit weight (37.83 g), while the highest juice (43.72%) and pulp content (84.67%) were noted in Haematocarpus validus and Myrica esculenta, respectively. Maximum total soluble solids (18.27±1.49%), total sugar (11.27±1.26%), moisture content (88.39±1.85%), ascorbic acid content (63.82 mg/100 g), total carotenoids (18.47 mg/100 g), and total monomeric anthocyanin (354.04 mg/100 g) were recorded in H. validus. Docynia indica had the highest total phenolic content (19.37 mg GAE/g), while H. validus recorded the highest total flavonoids and flavanol content. The antioxidant activities of the different fruits ranged from 0.17 to 0.67 IC50 for DPPH activity and 3.59 to 13.82 mg AAE/g for FRAP. These fruits had attractive pigmentation of both pulp and juice and were a good potential source for the extraction of natural edible colour in the food industry. The fruits also possess high market prices; Prunus nepalensis fetched $ 34.10 - $ 141.5 per tree. Therefore, these fruits are rich sources of antioxidants, and pigments and have a high market value for livelihood and nutritional security.